Procalcitonin as a biomarker of cardiac implantable electronic device pocket infection: a prospective validation study. (19th May 2022) - Knoll, K; Oconnor, M; Chouchane, A; Haller, B; Schaarschmidt, C; Bock, M; Foerschner, L; Froehlich, R; Kottmaier, M; Bourier, F; Reents, T; Hessling, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The implantation of cardiac implantable electronic devices (CIEDs) such as pacemakers and implantable cardioverter-defibrillators is increasing along with the complexitly of these devices. CIED infection is an uncommon, but severe complication associated with the presence of a device and is associated with a high mortality and morbidity. Lead-related infections and frank endocarditis are associated with a systemic inflammatory response and, in general, are readily identified. Isolated pocket infections do not produce such a systemic response and are thus more complex to diagnose. There is a reliance on clinical accumen and examination of local signs of infection. There is thus a need for a reliable biomaker to help identify cases of pocket infection. Aim: Our group have previously shown procalcitonin (PCT) to be a potentially useful biomaker in the clinial situation of possible pocket infection. We aim to prospectively validate the proposed cut-off value of 0.05ng/ml for the procalcitonin (PCT) biomaker in an independent cohort, which we have previously identified as showing promise in this clinical situation. Methods: In this prospective case-control validation study the PCT levels of 81 patients with confirmed pocket infections were compared to 81 controls, matched for age and renal function, presenting for elective generator replacement or lead revision unrelated to infection. Exclusion criteria included: concomitant infectious or inflammatory diseases, end-stage renal failure, active malignancy or receiving immunosuppressive therapy. Results: A PCT over 0.05 ng/ml was found in 68% (n= 55) of pocket infections and 24% (n= 19) of controls. Using the predefined cut-off value of 0.05 ng/ml PCT had a sensitivity of 68% and a specificity of 77% for diagnosing pocket infections. ROC analysis revealed area under the curve of 0.752 (standard error 0.039, p <0.001 ) for PCT. In patients presenting with minimal infective signs the sensivity remained high (67% vs 70% with extensive inflammation) and similarly remained high in thus who had received anti-biotic therapy prior to PCT sampling (65% vs 69%). Conclusion: PCT is a potentially useful biomarker to aid the diagnosis of a pocket infection when used with the prospecitvely validated cut-off value of 0.05ng/ml. The sensitivity of the PCT positive result remained high even in patients pre-treated with antibiotics or with minimal clinical signs of inflammation.